Spore special issue: Making the connection: The rise of agricultural value chains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
The 2012 Spore Special Issue is dedicated to value chains – arguably the best way for smallholder farmers to become integrated into modern markets. This issue tries to clear some of the confusion surrounding value chains and provides a broad picture of interesting innovations in ACP countries. It contains four chapters which, through the use of expert narratives, case studies and field reports, explain value chains, highlight the importance of the producer-consumer relationship, and look at strategic choices and the essential role of a favourable environment.